THE MEANING OF STERILITY IN THE PATRIARCHAL CYCLE - Chwarts, Suzana (PRINCIPIA, 2009)
This paper focuses on the concept of sterility as idealized in the Biblicaltext and exemplified in the stories of Sarah and Abraham, Rebecca, Leah, Racheland Jacob. My analysis of these stories leads to the hypothesis that sterility is oneof the foundational themes of Israel’s ancient past, by condensing some of themain obstacles inherent to the emergency of a people who believe to be guided byGod. This new perspective on sterility was achieved by focusing on the spectrumof meanings of the Hebrew root ‘qr, which includes infertility and uprooting;these, added to famine in the land, are experiences that will shape the religiousconscience of Israel. This approach amplifies the perception of sterility in theHebrew Bible, as it emerges from the text as a liminal state of deprivation , inopposition to the contents of the divine oath to the patriarchs (progeny and land).But even while enclosing lack of productivity, weakness and death, which have anegative value, Biblical sterility is not a closed circle, but a space open to potentiality,where divine revelation occurs. God reveals himself through sterility and in sterility.The originality and the notion of specificity in the biblical idea of sterility lie in thiscyclical trait, which breaks the circumscription and negative orientation of sterility.The Bible presents sterility as a transitory state, an area for individual and corporatetransformation of status. In an ideological system, such as ancient Israel’s, wherecontractual relations replace natural relations, sterility functions as a powerfulsymbol of the relationship among men and between men and God. And this may bethe reason why sterile matriarch’s traditions were continually re-interpreted, fromthe 10th century BCE. until the 1st century CE, and could be adapted to newcontexts and make sense to distinct communities, particularly in times of crisis andtransition.